2006
DOI: 10.1377/hlthaff.25.5.1371
|View full text |Cite
|
Sign up to set email alerts
|

How Direct-To-Consumer Television Advertising For Osteoarthritis Drugs Affects Physicians’ Prescribing Behavior

Abstract: Concern about the potential pernicious effect of direct-to-consumer (DTC) drug advertising on physicians' prescribing patterns was heightened with the 2004 withdrawal of Vioxx, a heavily advertised treatment for osteoarthritis. We examine how DTC advertising has affected physicians' prescribing behavior for osteoarthritis patients. We analyzed monthly clinical information on fifty-seven primary care practices during 2000-2002, matched to monthly brand-specific advertising data for local and network television.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
47
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(53 citation statements)
references
References 10 publications
6
47
0
Order By: Relevance
“…5 A nationally representative survey in 2003 indicated that one-third of American adults had discussed a DTCA medication with their physician, and that 1 in 10 had received a prescription in response to their inquiry. 2 Proponents of DTCA suggest it can inform consumers of new therapies, [6][7][8] motivate them to seek care, 8 give them more autonomy in weighing Bennett Parnes, MD 1,2 Peter C. Smith, MD 1,4 Christine Gilroy, MD 5 Javan Quintela, BS 6,7,9 and lower drug costs by increasing competition. 6 Critics argue that DTCA provides incomplete and biased information, 10,11 leads to inappropriate prescribing, 12 increases costs as a result of the added costs of advertising, and consumes time in the physician-patient encounter.…”
mentioning
confidence: 99%
“…5 A nationally representative survey in 2003 indicated that one-third of American adults had discussed a DTCA medication with their physician, and that 1 in 10 had received a prescription in response to their inquiry. 2 Proponents of DTCA suggest it can inform consumers of new therapies, [6][7][8] motivate them to seek care, 8 give them more autonomy in weighing Bennett Parnes, MD 1,2 Peter C. Smith, MD 1,4 Christine Gilroy, MD 5 Javan Quintela, BS 6,7,9 and lower drug costs by increasing competition. 6 Critics argue that DTCA provides incomplete and biased information, 10,11 leads to inappropriate prescribing, 12 increases costs as a result of the added costs of advertising, and consumes time in the physician-patient encounter.…”
mentioning
confidence: 99%
“…Although there is considerable variation in the results from prior studies based on differences in analytic approach and definitions of exposures and outcomes, the preponderance of evidence suggests that DTCA is associated with increases in consumer demand (17), physician diagnoses (9), the number of prescriptions (3,(8)(9)(10), prescription sales (10), therapeutic class size (18), and physician visits (19,20). Despite the insights from these prior studies, most examined DTCA exposure based on national expenditures, and many examined a single aggregated outcome, such as prescription volume alone.…”
Section: Discussionmentioning
confidence: 99%
“…For complete information, other ads in magazines or newspapers should be combined with broadcast ads. Moreover, one third of ads provided beneficial information, e.g., prevalence, understanding of misconception, risk factors and supportive treatment (appropriate lifestyle) and also increased discussion between users and their physicians which led to patients reeducation [17].…”
Section: Direct-to-consumer Promotion 1a Market Size and Sharementioning
confidence: 99%